Peran Sertifikasi Ecolabel dalam Membentuk Citra Perusahaan dan Dampaknya pada Intensi Pembelian Konsumen (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
Ecolabel certification is the process of assessing the environmental performance of a product or service by an independent and credible third party. Ecolabel certification can help companies to improve their positive image in the eyes of consumers, while demonstrating their commitment to environmental conservation. This study aims to analyze the role of ecolabel certification in shaping corporate image and its impact on consumer purchase intentions. The method used is an online survey of 385 respondents who have purchased products or services with ecolabels. The results show that ecolabel certification has a positive and significant effect on corporate image and consumer purchase intention. The implication is that companies can utilize ecolabel certification as an effective marketing strategy to increase competitive advantage and consumer loyalty.